Private Lease Apartment - A Better Potential Through Build-then-sell Approach - Ainur Zaireen Zainudin; Norhafiza Abdullah; Norhidayah Md Yunus; Salfarina Samsudin; Nur Emma Mustaffa; Siti Radiaton Adawiyah Zakaria; Fatin Afiqah Md Azmi; Aminah Mohsin; Noorfajri Ismail (Malaysian Institute of Planners, 2024)
Indexed by Scopus/MyCite